(3QSGdI aj GdYed HGdLjH GdSJjfi HdG eQi hdGeOGQs
(3ChdgG (B:s
(3HYO GdHSedI (B: (3agPg QSGdI eNJUQg ai GdYed HGdLjH GdSJjf HdG eQi hdG eOGQ s
(3BNQgG (B:s
(3EPG cGf Gdejd ai LgI YQV GdHdO hLgg SYI GdeTQb LgI Gdejd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B46 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B138) s
Keywords: (3Gdadcs